The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2796.2004.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of chronic Philadelphia chromosome negative (Ph‐) myeloproliferative disorders in the city of Göteborg, Sweden, during 1983–99

Abstract: Abstract. Johansson P, Kutti J, Andréasson B, SafaiKutti S, Vilén L, Wedel H, Ridell B (Sahlgrenska University Hospital, Göteborg, Sweden). Trends in the incidence of chronic Philadelphia chromosome negative (Ph-) myeloproliferative disorders in the city of Göteborg, Sweden, during 1983-99. J Intern Med 2004 256: 161-165. Objective. In the literature the incidence rates for the chronic Philadelphia chromosome negative (Ph-) myeloproliferative disorders (MPD) are known to vary extensively; only a few studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 15 publications
5
42
0
5
Order By: Relevance
“…20,22 The mean age at diagnosis in our series was close to that in both the Swedish and Danish populations but approximately 5 to 10 years younger than in patients from the South Thames area. 6,22 Data on long-term survival, such as over 15 or 20 years, are quite rare in the literature, especially from populationbased studies. In AML, the most remarkable finding of our series was the tapering of the survival increase observed in the 2000-2004 period.…”
supporting
confidence: 75%
“…20,22 The mean age at diagnosis in our series was close to that in both the Swedish and Danish populations but approximately 5 to 10 years younger than in patients from the South Thames area. 6,22 Data on long-term survival, such as over 15 or 20 years, are quite rare in the literature, especially from populationbased studies. In AML, the most remarkable finding of our series was the tapering of the survival increase observed in the 2000-2004 period.…”
supporting
confidence: 75%
“…6 The disease primarily affects the elderly, with a median age, at diagnosis, of 67 years in one study 7 and 75 years in another. 8 Several prognostic scores have been published. The 'Lille score' was the most commonly used at the time of study design and includes Hb (o10 g/dL) and WBC counts (o4 or 430 Â 10 9 /L).…”
Section: Introductionmentioning
confidence: 99%
“…MPD statistics are currently not measured by Surveillance, Epidemiology and End Results Program of the National Cancer Institute, an important source of information on cancer incidence and survival in the United States, even though the incidence of these diseases matches or exceeds other measured cancers such as multiple myeloma and CML. The most complete statistics to date on MPD incidence come from a Swedish study in 2001, which showed that the annual incidence/1 00 000 population for PV, ET and PMF are 2.8, 1.5 and 0.4, respectively (Johansson et al, 2004). The prevalence of PV, ET and PMF in the United States has been estimated to be 80-1 00 000 cases, with B2-5 new cases per 1 00 000 individuals per year (Kutti and Ridell, 2001;Tefferi and Vardiman, 2007).…”
Section: Ph(à) Mpds: Pv Et and Pmfmentioning
confidence: 99%